ANALISIS SWOT PERKEMBANGAN PERBANKAN SYARIAHDI INDONESIA - Sodiq, Amirus (IAIN Kudus, 2017)
This research aims to analyze the development of Islamic banking in Indonesia by SWOT analysis, the research is a qualitative research using secondary data and the result concludes that among the strength of sharia banking is conformity with the principles of sharia, resistant to crisis, has a legal system. While the weaknesses on human resources and technical problems, the opportunity is the increasing awareness of the religious community and knowledge about usury,and the threat is sharia banking can be linked with religious fanaticism and the parties disturbed by the existence of Islamic banks because the source of his income from conventional banking.Keywords:SWOT,awareness,fanaticm,islamic banking